Clearing of circulating tumour DNA predicts clinical response to osimertinib in EGFR mutated lung cancer patients. (May 2020) - Boysen Fynboe Ebert, Eva; McCulloch, Tine; Holmskov Hansen, Karin; Linnet, Hanne; Sorensen, Boe; Meldgaard, Peter
Graphical abstract: Highlights: EGFR mutations were present in ctDNA at PD to first line TKI in 70 % of cases. T790 M in ctDNA was consistently completely cleared on osimertinib treatment. Sensitizing EGFR mutations were cleared in 62 % of cases. Non-clearers had significantly shorter PFS and lower ORR and DCR than clearers. Initial monitoring of ctDNA predicted outcome to osimertinib. Abstract: Objectives: Tyrosine kinase inhibitors (TKIs) are first line treatment choices for patients with epidermal growth factor receptor (EGFR) mutated non-small cell lung cancer (NSCLC). However, responses vary among patients, therefore good biomarkers predicting better responses are required. EGFR mutations are detected in the blood from patients as circulating tumour DNA (ctDNA). Studies have shown that clearing ctDNA during first line TKI treatment predicts outcomes for first and second generation TKI treatments. We aimed to investigate the effects on outcome measures of ctDNA clearing in subsequent treatment lines to treatment with the third generation TKI osimertinib. Methods: In total, 225 patients were included in a prospective, multicentre study, where consecutive blood samples were monitored for EGFR mutations during systemic treatment lines, using the Cobas® EGFR mutation test v2. This study focused on EGFR mutations in ctDNA of 82 systemically pre-treated patients receiving osimertinib. Results: Clearing all EGFR mutations from the blood after osimertinib treatment, significantly predicted progression-free survival, objective response rates and disease control rates. Primary sensitising EGFR mutations were found in ctDNA in 70 % of patients, and were accompanied by the T790 M mutation in nearly two thirds of cases. The T790 M mutation was cleared in all cases, while the accompanying sensitising mutations did not necessarily clear. However, T790 M clearing without simultaneously clearing of the primary sensitising mutation did not predict clinical responses. Neither the detection of T790 M before osimertinib treatment, nor the presence of EGFR mutations at the time of osimertinib initiation predicted clinical outcomes. Conclusion: The clearing of EGFR mutations in ctDNA after osimertinib treatment initiation in patients with advanced NSCLC is useful as a positive predictor of clinical outcome.